The No Order Effect of Accounting Information - Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
This study models the behavior of investor reactions to joint dividend and earnings surprises. Using Hogarth and Einhorn’s (1992) belief-adjustment theory, it predicts that when dividend and earnings surprises have the same signs (consistent evidence),  whether dividend surprises follow or precede earnings surprises, has no effect on stock returns (the ‘no-order’ effect hypothesis).This study finds evidence for the ‘no-order’ effect hypotheses for consistent positive evidence. The impact of consistent positive evidence is unaffected by the order of announcements. The finding of this study has a important implication for firm’s announcement policy. If a firm likes to announce two “good news” information, the order of the announcement does not matter in affecting its stock price. In this case, the firm can announce a positive dividend surprise first followed by a positive earnings surprise or a positive earnings surprise first followed by a positive dividend surprises without any effect to the stock price.